2016
DOI: 10.1016/j.psychsport.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Examining the interactive effects of coach-created empowering and disempowering climate dimensions on athletes’ health and functioning

Abstract: 29Based in Duda's (2013) hierarchical and multidimensional conceptualisation of the 30 motivational climate, the purpose of this study was to examine whether a coach-created

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 49 publications
5
66
1
1
Order By: Relevance
“…The positive correlations observed between the psychobiosocial states index and the indices of the other summated scales (i.e., PACES, TIMCPEQ, and SIMS) also support the pattern of relationships. This is consistent with an integrative approach in physical education and sport that emphasizes an empowering task-involving, autonomy supportive, and socially supportive motivational climate, in contrast to a disempowering ego-involving and controlling motivational climate (Duda, 2013; Appleton and Duda, 2016).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The positive correlations observed between the psychobiosocial states index and the indices of the other summated scales (i.e., PACES, TIMCPEQ, and SIMS) also support the pattern of relationships. This is consistent with an integrative approach in physical education and sport that emphasizes an empowering task-involving, autonomy supportive, and socially supportive motivational climate, in contrast to a disempowering ego-involving and controlling motivational climate (Duda, 2013; Appleton and Duda, 2016).…”
Section: Discussionsupporting
confidence: 80%
“…The motivational climate influences the individual goal orientation and the adoption of a certain goal of action and behavior (Roberts and Treasure, 2012). A task-involving climate was consistently positively linked to intrinsic motivation, enjoyment, and adaptive motivational processes (Liukkonen et al, 2010; Barkoukis and Hagger, 2013), whereas an ego-involving climate was shown to determine maladaptive consequences (Appleton and Duda, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Also, team medical staff should focus particular attention to athletes who may be suffering from chronic injuries or medical conditions, in addition to athletes with significant concussive histories. Given that positive relationships between athletes and their coaches facilitates help-seeking, coaches are in a unique position to raise awareness about the clinical manifestations of symptoms and normalize psychological distress as a commonly occurring condition, which may promote positive behavior change and decrease stigma associated with seeking mental health services (Appleton & Duda, 2016; Gulliver et al, 2012; Schwenk at el., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of whether working with an individual athlete or in team sports, coaches play a crucial role in an athlete’s physiological and psychological health [ 45 47 ]. Although some coaches work together with different health practitioners to ensure optimal health and performance of their athlete(s), there are still coaches that do not acknowledge the importance of their athletes’ nutrition.…”
Section: Reason For Lea and Prevalence In Different Sports Across Sexmentioning
confidence: 99%